Measurement of Residual Stresses in Nuclear-grade Zircaloy-4(R) Tubes—Effect of Heat Treatment - Rasty, J.; Le, X.; Baydogan, M.; Cárdenas-García, J. F. (Springer Science and Business Media LLC, 2007)
Nuclear-grade Zircaloy-4(R) tubes are produced by a unique manufacturing process known as pilgering, which leaves the material in a work-hardened state containing a pattern of residual stresses. Moreover, such tubes exhibit elastic anisotropy as a result of the pilgering process. Therefore, standard equations originally proposed by Sachs (Z Met Kd, 19: 352–357, 1927; Sachs, Espey, Iron Age, 148: 63–71, 1941). for isotropic materials do not apply in this situation. Voyiadjis et al. (Exp Mech, 25: 145–147, 1985) proposed a set of equations for treating elastically anisotropic materials, but we have determined that there are discrepancies in their equations. In this paper, we present the derivation for a set of new equations for treating elastically anisotropic materials, and the application of these equations to residual stress measurements in Zr-4(R) tubes. To this end, through thickness distribution of residual stress components in as-received and heat treated (500°C) Zr-4(R) tubes was measured employing the Sachs’ boring-out technique in conjunction with electrochemical machining as the means of material removal, and our new equations. For both as-received and the heat treated materials, the axial and tangential residual stresses were significantly higher than the radial and shear residual stresses. The largest residual stress was the tangential stress component in the as-received material, showing a tensile value at the outer surface and a compressive value at the inner surface. At high values of von Mises equivalent stress, the principal directions of residual stress coincided with the principal axes of the tube for the as-received material, as well as for the material heat treated at 500°C.